Tingkat Kebugaran Jasmani Siswa Ekstrakurikuler Bola Voli Berdasarkan Tes Kebugaran Pelajar Nusantara - Ahmad Badaruzzaman; Ardhi Mardiyanto Indra Purnomo; Moh. Nur Kholis; Muhdhofar Soliq Sidiq (Jurnal Simki Postgraduate, 2026)
Physical fitness is a fundamental prerequisite for students participating in sports extracurricular activities, as it directly supports endurance, movement quality, and overall learning readiness. Despite growing recognition of physical fitness importance among school-age adolescents, the physical fitness status of students engaged in volleyball extracurricular activities in rural Indonesian schools remains poorly documented. This study aimed to describe the physical fitness levels of volleyball extracurricular students at SMP Negeri 1 Pule, Trenggalek, using the Tes Kebugaran Pelajar Nusantara (TKPN) as a standardized national fitness assessment instrument. A quantitative descriptive survey design was employed. The total population of 32 active volleyball extracurricular members (14 male, 18 female) was included using saturated sampling. Data were collected across five TKPN components: body mass index (BMI), V sit and reach, sit-up, squat thrust, and PACER. Descriptive statistical analysis classified scores into TKPN normative categories. Results revealed that 21 students (65.63%) had good nutritional status based on BMI. However, other fitness components were suboptimal: V sit and reach showed the largest proportions in the very low and moderate categories (37.50% each); sit-up placed 24 students (75.00%) in the very low category; squat thrust placed 19 students (59.38%) in the low category; and PACER placed all 32 students (100.00%) in the very low category. These findings indicate that extracurricular volleyball participation has not ensured balanced fitness development, particularly in muscular endurance and cardiorespiratory endurance. Schools are urged to implement more structured, measurable, and progressive physical conditioning programs.